2009
DOI: 10.1111/j.1747-0765.2009.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite (phosphorous acid): Fungicide, fertilizer or bio-stimulator?

Abstract: Phosphite (; Phi), a reduced form of phosphate (; Pi), is widely marketed as either a fungicide or fertilizer or sometimes as a biostimulant. This is confusing for both distributors and growers. The present paper explores data from various studies to clarify that Phi does not provide plant P nutrition and thus cannot complement or substitute Pi at any rate. In addition, Phi itself does not have any beneficial effect on the growth of healthy plants, regardless of whether it is applied alone or in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 26 publications
7
97
0
4
Order By: Relevance
“…** and *: significant at 1 % and 5 % by the F test, respectively. proportions higher than 25 % in the solution were toxic to bean plants, as demonstrated visually by the shortening and thickening of roots and by the chlorosis in young leaves, as also observed for other crops (Varadarajan et al 2002, Thao & Yamakawa 2009). This results in a lower production of dry matter (Araújo et al 2013), which explains the lower accumulation of nutrients.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…** and *: significant at 1 % and 5 % by the F test, respectively. proportions higher than 25 % in the solution were toxic to bean plants, as demonstrated visually by the shortening and thickening of roots and by the chlorosis in young leaves, as also observed for other crops (Varadarajan et al 2002, Thao & Yamakawa 2009). This results in a lower production of dry matter (Araújo et al 2013), which explains the lower accumulation of nutrients.…”
Section: Resultssupporting
confidence: 60%
“…It was observed that providing P exclusively in the form of phosphite (Phi) decreases the dry mass of common bean by about 95 %. One possible explanation for the phytotoxicity could be the fact that phosphite, when phosphate is deficient, increases the concentration of poly and pyrophosphates and inhibits several enzymes of the glycolysis and pentose phosphate pathway, thus interfering with the metabolism of P (Varadarajan et al 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have obtained evidence that foliar treatment with Phi increased the length of crop cycle and that could improve tuber yield (Lobato et al 2008). Recently, Thao and Yamakawa discussed in a review article the role of Phi as a fungicide, fertilizer or bio-stimulator and showed that Phi can act with at least one of these properties in different study systems (Thao and Yamakawa 2009).…”
mentioning
confidence: 99%